Protein Disulfide Isomerase in Thrombosis - Chiu, Joyce; Passam, Freda; Butera, Diego; Hogg, Philip J. (Seminars in Thrombosis and Hemostasis, 2015)
Protein disulfide isomerase (PDI) is a 57-kDa oxidoreductase that facilitates cysteine thiol reactions inside and outside the cell. It mediates reduction or oxidation of protein disulfide bonds, thiol/disulfide exchange reactions, and transfer of NO from one protein thiol to another. It also has chaperone properties. PDI is actively secreted by most, if not all, of the cell types involved in thrombosis, binds to integrins on the cell surface, and circulates as a soluble protein in blood. It plays a critical role in thrombosis in mice and presumably the same role in human thrombosis. Eight proteins involved in thrombosis have been identified as PDI substrates; however, the role of this oxidoreductase in this process is not fully understood. Novel small-molecule PDI inhibitors have been developed and are being evaluated as antithrombotics in clinical trials. This combination of ongoing laboratory and clinical studies will greatly accelerate the pace of discovery and targeting of PDI function in thrombosis.
Keywords: thrombosis; protein disulfide isomerase; allosteric disulfides; antithrombotics